2011
DOI: 10.1021/bi201460j
|View full text |Cite
|
Sign up to set email alerts
|

The DinB Superfamily Includes Novel Mycothiol, Bacillithiol, and Glutathione S-Transferases

Abstract: The superfamily of glutathione S-transferases has been the subject of extensive study but Actinobacteria produce mycothiol (MSH) in place of glutathione and no mycothiol S-transferase (MST) has been identified. Using mycothiol and monochlorobimane as substrates a MST activity was detected in extracts of Mycobacterium smegmatis and purified sufficiently to allow identification of MSMEG_0887, a member the DUF664 family of the DinB superfamily, as the MST. The identity of the M. smegmatis and homologous Mycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 53 publications
(140 reference statements)
1
97
0
1
Order By: Relevance
“…When we followed the fate of the fluorescent alkylating agent monochlorobimane, which is less chemically reactive and thus would require a BST, analogous to a GST, to catalyse its conjugation to BSH, the mercapturic acid of the bimane was detected intracellularly and extracellularly, indicating the presence of a BST, which catalyses the conjugation of monochlorobimane with BSH to produce BSmB. Recently, we have identified and characterized a B. subtilis BST which is able to catalyse the reaction of monochlorobimane with BSH; whether the S. aureus homologue does the same remains to be seen (Newton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When we followed the fate of the fluorescent alkylating agent monochlorobimane, which is less chemically reactive and thus would require a BST, analogous to a GST, to catalyse its conjugation to BSH, the mercapturic acid of the bimane was detected intracellularly and extracellularly, indicating the presence of a BST, which catalyses the conjugation of monochlorobimane with BSH to produce BSmB. Recently, we have identified and characterized a B. subtilis BST which is able to catalyse the reaction of monochlorobimane with BSH; whether the S. aureus homologue does the same remains to be seen (Newton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A protein (SCO7269) belonging to the DinB (DNA damage-inducible) superfamily (44) and bearing a mycothiol-dependent maleylpyruvate isomerase Nterminal domain was found to be present in larger amounts in the ppk mutant than in the wt strain. Proteins of this family were shown to catalyze thiol-dependent detoxification reactions (45).…”
Section: Proteomic Studiesmentioning
confidence: 99%
“…During the preparation of the present study the characterization of three additional enzymes in DinB superfamily was reported to suggest that thiol-dependent S-transferase activity is dominant in this family, including MSH, bacillithiol (BSH), and GSH S-transferases (32). In particular, B. subtilis YfiT, mentioned above, was shown to have BSH S-transferase activity (32). As shown in the phylogenetic tree of the DinB superfamily in Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The complete loss of enzyme activity in three BagL mutants indicated that the three histidines are necessary for its activity and probably function in binding with Ni 2Ï© . During the preparation of the present study the characterization of three additional enzymes in DinB superfamily was reported to suggest that thiol-dependent S-transferase activity is dominant in this family, including MSH, bacillithiol (BSH), and GSH S-transferases (32). In particular, B. subtilis YfiT, mentioned above, was shown to have BSH S-transferase activity (32).…”
Section: Discussionmentioning
confidence: 82%